Butterfly defect : how globalization creates systemic risks, and what to do about it - Goldin, Ian, 1955-; Mariathasan, Mike, 1982- (Princeton (USA) Oxford (UK) Princeton University Press, 2014)
"Global hyperconnectivity and increased system integration have led to vast benefits, including worldwide growth in incomes, education, innovation, and technology. But rapid globalization has also created concerns because the repercussions of local events now cascade over national borders and the fallout of financial meltdowns and environmental disasters affects everyone. The Butterfly Defect addresses the widening gap between systemic risks and their effective management. It shows how the new dynamics of turbo-charged globalization has the potential and power to destabilize our societies. Drawing on the latest insights from a wide variety of disciplines, Ian Goldin and Mike Mariathasan provide practical guidance for how governments, businesses, and individuals can better manage risk in our contemporary world. Goldin and Mariathasan assert that the current complexities of globalization will not be sustainable as surprises become more frequent and have widespread impacts. The recent financial crisis exemplifies the new form of systemic risk that will characterize the coming decades, and the authors provide the first framework for understanding how such risk will function in the twenty-first century. Goldin and Mariathasan demonstrate that systemic risk issues are now endemic everywhere--in supply chains, pandemics, infrastructure, ecology and climate change, economics, and politics. Unless we are better able to address these concerns, they will lead to greater protectionism, xenophobia, nationalism, and, inevitably, deglobalization, rising conflict, and slower growth. The Butterfly Defect shows that mitigating uncertainty and systemic risk in an interconnected world is an essential task for our future."--Jacket.
Globalization and risk in the twenty-first century -- The financial sector with Co-Pierre Georg and Tiffany Vogel -- Supply chain risks -- Infrastructure risks -- Ecological risks -- Pandemics and health risks -- Inequality and social risks -- Managing systemic risk.
Includes bibliographical references and index.
Keywords: Risk management; Crisis management; Globalization; Political science -- Globalization; Business & Economics -- Development -- Economic Development; Business and economics -- International -- General; Political science -- General; Crisis management; Globalization; Risk management